â€œAl-'Arabiyyatu Baina Yadaikâ€: Textbook by Abdul Rahman ibn Ibrahim Al-Fawzan, Etc. - Abid Nurhuda; Afiffah Vinda Prananingrum (Sukma: Jurnal Pendidikan)
The text book Al-’Arabiyyah Baina Yadaik is one type of Arabic learning book that is still often used in the world of Arabic language education in Indonesia. This book presents many topics about elements of Islamic and Arabic culture with interesting presentations and has a very high educational value. Therefore, this book is very interesting to study and analyze whether each topic presented is in accordance with language competence and whether the contents of the material listed are relevant to the correct textbook standards. This type of research is literature research with data collection techniques in the form of documentation techniques. The analysis technique uses content analysis techniques. Al-’Arabiyah Baina Yadaik is devoted to non-Arabic learners. Compiled by presenting several competencies such as:language skills (Kifayah al-lughowiyah), communication skills (Kifayah ittisholiyyah), and cultural skills (Kifayah tsaqofiyah). Served with a language maharoh which consists of two things, namely language skills (istima’, kalam, kitabah, and qiro’ah) and three elements in language, namely sound (al-aswat), sentence structure (al-tarakib) and vocabulary (al-tarakib). -mufradat). And has met CEFR standards at level B1 and B2.